Intrathoracic gastric volvulus: an autopsy case report - Cristiane Rúbia Ferreira; Linda Ferreira Maximiano; Victor Manuel Lobo dos Santos; João Augusto dos Santos Martines (University of São Paulo, 2013)
First described by Berti in 1866, gastric volvulus (GV) is an uncommon and potentially lethal entity. GV occurs when the stomach twists by more than 180º resulting in obstruction of the alimentary tract, visceral ischemia, necrosis, and perforation. It is classified according to the rotation axis in organoaxial, mesenteroaxial or a combination of both. The clinical presentation can be acute, and is usually severe or chronic, which sometimes may be asymptomatic. It predominantly occurs in the fifth decade of life, but children, mainly those under the age of 1 year, may be affected. No ethnicity or gender was observed to show predominance. This entity is related to gastric, diaphragmatic disorders as well as laxity of gastric ligaments. Acute GV may complicate with incarceration and strangulation of the stomach when gastric necrosis ensues. These cases show a mortality rate of 60%. The authors report the fatal case of a surgically treated GV in a 43-year-old female patient who looked for medical care only after 1 month of initial symptoms. Diagnosis was confirmed with a thoracic and abdominal axial computed tomography. Besides the entire stomach being herniated and twisted into the thoracic cavity, the pancreas was pulled up through the hiatal orifice, provoking acute pancreatitis. Because of gastric necrosis and perforation, gastroenteric fluid drained into the mediastinum and left pleural space. The postoperative outcome was unfavorable resulting in the patient's death. The authors call attention to the severeness of the disease, and therefore the need of precocity of diagnosis and surgical treatment.